Simulated transactions : the requirement of 'commercial substance' to determine simulation as enunciated in the NWK -case- the established substance over form doctrine renovated or a mere indivator of a concealed transaction? - Louw, C (Adv.) (University of Pretoria, 2014)
Dissertation (LLM)--University of Pretoria, 2013.